2018
DOI: 10.1002/nau.23828
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of lower urinary tract symptoms and overactive bladder in men and women over 18 years old: The Colombian overactive bladder and lower urinary tract symptoms (COBaLT) study

Abstract: Prevalence of lower urinary tract symptoms and overactive bladder in men and women over 18 years old: The Colombian overactive bladder and lower urinary tract symptoms (COBaLT) study Aims: To estimate the prevalence of LUTS and overactive bladder (OAB) in the Colombian population. Methods: A cross-sectional, population-based study was conducted in men and women ≥18 years using directed interviews and self-administered questionnaires in five main cities in Colombia. A sample size of 1054 subjects was estimated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 23 publications
(48 reference statements)
0
13
0
2
Order By: Relevance
“…Previously, we reported our preliminary experience in PVP and found it safe in patients under anticoagulants . In this study, 17.2% and 43.2% of the high‐risk patients were anticoagulated or under antiaggregation respectively, in contrast to 2% and 19% of the low‐risk group.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Previously, we reported our preliminary experience in PVP and found it safe in patients under anticoagulants . In this study, 17.2% and 43.2% of the high‐risk patients were anticoagulated or under antiaggregation respectively, in contrast to 2% and 19% of the low‐risk group.…”
Section: Discussionmentioning
confidence: 58%
“…9,25 Previously, we reported our preliminary experience in PVP and found it safe in patients under anticoagulants. 26 In this study, 17.2% and 43.2% of the high-risk patients were anticoagulated or under antiaggregation respectively, in contrast to 2% and 19% of the low-risk group. One of the first experiences with PVP and anticoagulated patients were reported by Sandhu et al, 27 In his small cohort of retrospective cases, no transfusions were required, no patients had postoperative significant hematuria, and none suffered clot retention.…”
Section: Discussionmentioning
confidence: 60%
“…Some published data suggest that Hispanic people have a higher risk of moderate or severe LUTS compared with Caucasians 8 . The few published studies of Latin American populations have provided epidemiological data, while overlooking the impact of OAB on work, QoL, and treatment-seeking behavior [9][10][11][12][13][14] . The Colombian Overactive Bladder and Lower urinary Tract symptoms (COBaLT) study of 1060 individuals aged 18-89 years found that OAB was reported by 31.8% of participants and had a severe effect on their QoL.…”
Section: Introductionmentioning
confidence: 99%
“…The Colombian Overactive Bladder and Lower urinary Tract symptoms (COBaLT) study of 1060 individuals aged 18-89 years found that OAB was reported by 31.8% of participants and had a severe effect on their QoL. OAB symptoms were assessed by the International Consultation on Incontinence Questionnaire Overactive Bladder (ICIQ-OAB) and followed the ICS definition 12 . Another study conducted in Porto Alegre, Brazil reported that OAB, according to the ICS definition, affected 18.9% of 848 individuals aged 15-55 years, with a statistically significantly greater incidence in females (23.2%) than males (14%) 14 .…”
Section: Introductionmentioning
confidence: 99%
“…4 En un reciente estudio en Colombia por Plata y cols., se determinó que la prevalencia de IUE en mujeres por encima de los 18 años es del 13,7%, siendo mayor (24,2%) en el grupo de mujeres mayores de 65 años. 5 Por su elevado costo financiero y el impacto en el bienestar social y QoL, esta patología debe considerarse un problema de salud pública. En cuanto al efecto de la IU en la QoL, se ha encontrado que altera múltiples esferas, entre ellas, la función sexual.…”
Section: Definiciones Y Epidemiologíaunclassified